Proposed Business Strategy in Toll Road Sector to Optimize Tariff Adjustments Process - Cicilia Andita Setya Permatasari (Green Publisher Indonesia, 2025)
This research aims to explore the company’s internal strengths and weaknesses, identify external opportunities and threats, and propose business strategies to improve the company’s condition in fulfilling SPM and achieve on-schedule toll tariff adjustment. Using a qualitative research method, this research combines primary data from in-depth interviews with the key internal stakeholders and secondary data from company’s documents including annual report, past internal studies, financial analysis report, company’s minutes of meeting, and relevant regulatory document. The research employs market analysis and several frameworks including PESTLE, The Five Forces Model, Competitor Analysis for external analysis, and VRIO and Value Chain for internal analysis. The result shows that the company possesses several internal strengths such as strong operational management capabilities, well established governance structure, strategic toll road asset, competent human resources, good initiative in innovation practices, and good reputation. However, these are outweighed by weaknesses including weak financial position reflected in its high debt to equity ratio and negative return on asset, heavy reliance on outsourced operations, lacks structured approach to innovation and has not yet developed the tools or system needed to fully optimize traffic. These weaknesses directly contribute to the SPM delays and inability to adjust tariff on time. Externally, the company faces political and legal uncertainty in toll road sector, macroeconomic slowdown leads to declining purchasing power, sensitive to price users and significant deviation between actual traffic and projection in concession agreements, even though opportunities exist through government development priorities in Gerbangkertosusila region